Polynomial interior-point algorithm for P horizontal linear complementarity problems - Asadi, S.; Mansouri, H. (Numerical algorithms, 2013)
In this paper an interior-point algorithm for P * ( κ ) horizontal linear complementarity problems is proposed that uses new search directions. The theoretical complexity of the new algorithm is calculated. It is investigated that the proposed algorithm has quadratically convergent with polynomial iteration complexity , coincide with the best known iteration bound for P * ( κ ) horizontal linear complementarity problems.